DETERMINAN PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PERUSAHAAN YANG TERGABUNG DI JAKARTA ISLAMIC INDEX - Lukman Effendy; Zuhrotul Isnaini; Isnawati Isnawati (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
This study aims to examine the determinants of the disclosure of Islamic social reporting of companies incorporated in the Jakarta Islamic Index. ISR determinants in this study are company size, profitability, leverage, board size, and company age. The population used in this study were all companies listed on the Jakarta Islamic Index (JII) for the period 2016 to 2018. The sampling method used was purposive sampling with a sample size of 51 company years. Data panel regression is used to achieve the goal. The results showed that company size, leverage, and the independent board of commissioners had a significant effect on the disclosure of Islamic social reporting. Meanwhile, profitability and company age show the opposite result.Keywords:Islamic Social Reporting; Firm Size; Leverage: Indepencent Board Director; Firm Age.